Putting the individual back into the corporate entrepreneurial process: studies in the determinants and consequences of employee entrepreneurial behaviour - Mustafa, Mike James (2020)
In order to survive and thrive in today’s modern and hyper-competitive environments, it is becoming increasingly necessary for firms to foster entrepreneurial and innovative activities. This particular thesis recognises that one of the most important sources of a firm’s entrepreneurialism and innovativeness is the entrepreneurial behaviour of its employees. However, many questions still remain in the existing literature with respect to how employees can become entrepreneurial, and what are the personal consequences for employees behaving entrepreneurially in the workplace. Broadly, this particular thesis to shed light on some of these important questions by utilising the JD-R model to examine the determinants and consequences of employee entrepreneurial behaviour. In order to address the objectives of thesis, four empirical studies were carried out.